An early Cambrian greenhouse climate - Hearing, Thomas W.; Harvey, Thomas H.P.; Williams, Mark; Leng, Melanie J.; Lamb, Angela L.; Wilby, Philip R.; Gabbott, Sarah E.; Pohl, Alexandre; Donnadieu, Yannick (American Association for the Advancement of Science, 2018)
The oceans of the early Cambrian (~541 to 509 million years ago) were the setting for a marked diversification of animal life. However, sea temperatures — a key component of the early Cambrian marine environment — remain unconstrained, in part because of a substantial time gap in the stable oxygen isotope (delta 18 O) record before the evolution of euconodonts. We show that previously overlooked sources of fossil biogenic phosphate have the potential to fill this gap. Pristine phosphatic microfossils from the Comley Limestones, UK, yield a robust delta 18 O signature, suggesting sea surface temperatures of 20° to 25°C at high southern paleolatitudes (~65°S to 70°S) between ~514 and 509 million years ago. These sea temperatures are consistent with the distribution of coeval evaporite and calcrete deposits, peak continental weathering rates, and also our climate model simulations for this interval. Our results support an early Cambrian greenhouse climate comparable to those of the late Mesozoic and early Cenozoic, offering a framework for exploring the interplay between biotic and environmental controls on Cambrian animal diversification.